2018
DOI: 10.1186/s13705-018-0152-5
|View full text |Cite
|
Sign up to set email alerts
|

A change in the wind? US public views on renewable energy and climate compared

Abstract: Background: Renewable energy development is a necessary step toward climate change mitigation, so these topics have often been linked. In US public discourse, however, they have somewhat different profiles-climate change views are tied closely to partisan identity, whereas renewable energy exhibits more cross-cutting appeal, and sometimes more cross-cutting opposition as well. To what extent are such differences reflected in survey data tracking rates of change, respondent characteristics, and local or regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 53 publications
3
28
0
Order By: Relevance
“…While global warming views are clearly relevant, it is not common practice to include this variable in the analyses of public energy preferences [55,70]. Past work with climate views included has found that believing that global warming is caused mostly by humans is significant for renewable energy support in some studies, but not in others [45,71,72], and that the public does consider emissions when weighing energy preferences [71]. Additionally, general environmental views have been found to influence energy preferences [4,5,10,73,74], though this is also not consistently measured across studies.…”
Section: Public Opinion Research On Energy Preferencesmentioning
confidence: 99%
“…While global warming views are clearly relevant, it is not common practice to include this variable in the analyses of public energy preferences [55,70]. Past work with climate views included has found that believing that global warming is caused mostly by humans is significant for renewable energy support in some studies, but not in others [45,71,72], and that the public does consider emissions when weighing energy preferences [71]. Additionally, general environmental views have been found to influence energy preferences [4,5,10,73,74], though this is also not consistently measured across studies.…”
Section: Public Opinion Research On Energy Preferencesmentioning
confidence: 99%
“…Physical danger can arise during the winter when icicles fall down from turbines [74•]. Concerns for a devaluation of land and decreasing property prices tend to rank higher in public opinion polls in developed countries [95,96], see also [97,98].…”
Section: Negative Externalitiesmentioning
confidence: 99%
“…The nationwide POLES survey took place in two stages just before and after the 2016 presidential elections, with little difference in the main response patterns. [23] The North Country survey took place in summer 2017, interviewing residents of four rural counties in northern New England. [24][25] Two other regional projects, covering New Hampshire and northeast Oregon, each involved a series of surveys carried out with independent random samples from 2010 or 2011 to 2018.…”
Section: Four Survey Projectsmentioning
confidence: 99%
“…The nationwide survey took place in 2016, with stages just before and after the presidential elections. The three regional surveys involve places with recent and controversial wind energy developments, as described by Hamilton et al[23] One of the regional surveys, in the North Country of northern New England, occurred in summer of 2017. The other two regional projects, in northeast Oregon and New Hampshire, each involved a series of surveys carried out over multiple years—2011 to 2015 in Oregon, and 2010 (climate) or 2012 (renewable energy) to 2017 in New Hampshire.…”
Section: Introductionmentioning
confidence: 99%